2018
DOI: 10.4103/0366-6999.226057
|View full text |Cite
|
Sign up to set email alerts
|

Management of Urinary Incontinence before and after Total Pelvic Reconstruction for Advanced Pelvic Organ Prolapse with and without Incontinence

Abstract: Background:The effectiveness of an anti-incontinence procedure concomitant with prolapse reconstruction for pelvic organ prolapse (POP) in preventing urinary incontinence (UI) after surgery remains controversial. Our study aimed to describe the incidence of pre- and postoperative UI for pelvic reconstructive surgery and evaluate the management of POP associated with UI.Methods:A total of 329 patients who underwent total pelvic reconstruction between June 2009 and February 2015 at a single institution were iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The reason may be that pelvic floor reconstruction strengthens the urination control ability in the middle segment of the urethra. [ 25 ] The results of the present study revealed that at 3 and 12 months after the operation, the BND was significantly smaller in the PAR group than in the TO group. This suggests that autologous pelvic floor reconstruction is better than TOs in improving BND and has a certain preventive effect on new SUI after the operation.…”
Section: Discussionmentioning
confidence: 47%
“…The reason may be that pelvic floor reconstruction strengthens the urination control ability in the middle segment of the urethra. [ 25 ] The results of the present study revealed that at 3 and 12 months after the operation, the BND was significantly smaller in the PAR group than in the TO group. This suggests that autologous pelvic floor reconstruction is better than TOs in improving BND and has a certain preventive effect on new SUI after the operation.…”
Section: Discussionmentioning
confidence: 47%
“…Recent studies report incidence rates of 22%-53% for persistent or worsened MUI symptoms postoperatively, but outcomes were not stratified by surgical type in these studies. 8,27 In our study, we reported on outcomes of MUI by POPonly versus POP and SUI surgery. The POP and SUI surgery group had a significantly lower rate of persistent MUI compared with those who had surgery for POP only.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of de novo UI after PRS has been reported as approximately 15%, whereas rates of resolution of UI symptoms after PRS with and without continence procedures are approximately 40%. [7][8][9][10] The relationship between PRS and incidence of postoperative UI has not been explored among patients with diabetes specifically. Given the unique risk profiles of patients with diabetes relative to UI, it is important to understand this population's risk of postoperative UI after PRS to ensure proper counseling.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Needleless straps, as a product of modern medical advancements, have been designed by Spanish doctors to further improve the technique[ 17 ]. The two ends of a T-type bag are used for the needle-free sling and as a whole are considered a "worker" type; the length of the sling is 11.4 cm, the width of the pockets at both ends is 2.2 cm, and the width of the middle of the sling is 1.2 cm.…”
Section: Discussionmentioning
confidence: 99%